Implementing student self‐video of performance. (10th September 2013) - Maloney, Stephen; Paynter, Sophie; Storr, Michael; Morgan, Prue
Summary Background: Resource and curriculum constraints within contemporary university programmes limit opportunities for supervision and feedback of student practice. This study investigated the technological challenges, solutions and educational rewards in implementing Web‐based student self‐video of performance as a method to foster the development of student self‐evaluation. Methods: Physiotherapy students (n = 60) in their final preclinical semester participated in the study. All students received guidelines for constructing and uploading self‐videos of performance to a Web‐based learning system. Students completed a reflective task on each video submission after receiving online tutor feedback and viewing an exemplar peer performance. Students completed a survey of their learning experiences and challenges in completing the learning tasks. Technical information on submissions was obtained in usage reports from the Web‐based learning system. Results: Students were successful in recording and uploading digital videos of performance for remote tutor review. Students and tutors encountered technical problems that could be rectified and potentially avoided through activity design. Students reported that the utility of Web‐based self‐video for enhancing clinical performance outweighed the additional time and effort required in participation. Conclusions: Web‐based student self‐video of performance, with remote tutor feedback and guided reflection, is a feasible method for increasing students' capacity for reflection and self‐evaluation. Although technical difficulties are inherent in any technology‐reliant activity, the students' increasing competence with emerging technologies encourage self‐video teaching and learning activities as a resource for facilitating clinical skill development.